PENGARUH PRODUK, HARGA, LOKASI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA DISTRO CLUB DI KOTA BOGOR - Osta Nababan, Benny; ., Jubaedi (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2019)
This study the sampling technique used accidental sampling technique and the samples of this study was 100 respondents. The results of the study show that the results of the partial hypothesis test prove that the product variable with a t-count value of 3,240> t-table value 1.66. With a significance value of 0.002 <0.05 a significance value smaller than 0.05 indicates that at the significance level of 5%, the hypothesis HO is rejected and Ha is accepted. Hypothesis test results simultaneously prove that together the factors of product, price, location and promotion have a positive and significant influence on consumer purchasing decisions Distro Club Kota Bogor. The results of multiple linear regression test obtained a regression equation that is Y = 5.743 + 0.399 X1 + 0.187 X2 + 0.010 X3 + 0.081 X4 which means that there is an increase in product, price, location and promotion as much as one unit will raise consumer purchasing decisions Distro Club City of Bogor. Whereas if there is no increase in product value, price, location and promotion then the value of the consumer purchasing decision Distro Club Bogor City will be constant at 5.743. The results of the coefficient of determination test obtained an adjusted R² value of 0.290, this shows that 29.0% purchasing decisions in Distro Club Bogor City influenced by the marketing mix while the remaining 71.0% purchasing decisions are influenced by other variables not examined in this research.